Howard Watkins with Yosemite Valley in Background - Watkins, Howard::::::::: (1985)
Howard Watkins wearing CAL Berkeley blue and gold T-shirt standing a Yosemite tunnel over look with Half-Dome and Bridalveil Falls in the background